Nanoimprint template adhesive and preparation method thereof
By using polyurethane modified acrylate resin and perfluoropolyether acrylate resin to form a nanoimprint template glue for crosslinked monomers, the problems of incomplete curing and poor mechanical properties are solved, and high-quality peeling and degluing effects are achieved. , suitable for multiple precision imprints, and is harmless to the environment and the human body.
Patent Information
- Application Number
- CN202411191109.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing nanoimprint template glue is prone to incomplete curing, poor mechanical properties and low strength during the curing and forming process, resulting in the problem of breaking the soft film during the demolding process, residual glue remaining on the master plate, and difficulty in cleaning.
Polyurethane modified acrylate resin and perfluoropolyether acrylate resin are used as the main raw materials to improve the strength and elasticity of the film layer by forming crosslinked monomers, and fluorocarbon diluents, multifunctional crosslinking agents, additives and Free radical initiator, nanoimprint template glue with good peeling and degluing effects were prepared.
It improves the phenomenon of incomplete curing, improves the elasticity and strength of the film layer, realizes overall peeling or solvent cleaning, removes the master glue, is suitable for multiple precision imprinting, and is harmless to the environment and the human body.
Smart Images

Figure CN119242246A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of nanoimprint technology, and in particular to a nanoimprint template glue and a preparation method thereof. Background Art
[0002] Nanoimprint technology is a process of transferring the microstructure on the master to the wafer. Specifically, the template glue is applied to the master, and then cured to obtain a soft film with the master pattern, and then the soft film is transferred to the wafer. In this process, the soft film, as a carrier with imprinting features, directly determines the quality of the wafer imprint pattern. To achieve high-quality imprint replication, a high-quality imprint template is required.
[0003] The existing nanoimprint template glue will not be fully cured during the curing process, and the polymer film layer formed after curing also has poor mechanical properties and low strength. Therefore, in the process of preparing the soft film, it is easy for the soft film to be damaged during the demolding process, residual glue will remain on the master, and the master will be difficult to clean. Summary of the invention
[0004] The present application provides a nanoimprint template glue and a preparation method thereof, aiming to solve the problem that the existing template glue is prone to residual glue on the master plate during the transfer process and is difficult to clean the residual glue on the master plate, as well as the problem that it is difficult to demold after imprinting.
[0005] In a first aspect, the present application provides a nanoimprint template adhesive, which is prepared from the following raw materials: polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional cross-linking agent, auxiliary agent, cationic initiator and free radical initiator.
[0006] In a second aspect, the present application provides a method for preparing a nanoimprint template glue, the preparation method comprising:
[0007] Provide polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator;
[0008] The nanoimprint template adhesive is prepared by using the polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator.
[0009] The present application provides a nanoimprint template glue and a preparation method thereof, wherein the nanoimprint template glue is prepared with polyurethane modified acrylate resin and perfluoropolyether acrylate resin as the main body, and the polyurethane modified acrylate resin and perfluoropolyether acrylate resin are used to form a cross-linking monomer, so that the nanoimprint template glue forms a firm three-dimensional cross-linking network after curing, thereby greatly improving the phenomenon of incomplete curing. The introduction of perfluoropolyether acrylate resin can also improve the elasticity and strength of the film layer, and reduce the surface energy of the film layer. After film formation, the film layer can be peeled off as a whole or washed off with a solvent, so that the film layer has a good peeling and degumming effect, and can also achieve the removal of residual glue on the master plate, which is conducive to multiple precision imprinting. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0011] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a nanoimprint template glue provided in an embodiment of the present application;
[0012] Figure 2 It is a schematic flow chart of another embodiment of a method for preparing a nanoimprint template glue provided in an embodiment of the present application. DETAILED DESCRIPTION
[0013] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0014] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0015] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the application. As used in this application specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0016] It should be further understood that the term “and / or” used in the specification and appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0017] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0018] Template glue is a very important preparation material in the nanoimprint process. As the initial carrier of the imprint feature, the template glue directly determines the quality of the imprint pattern. To achieve high-quality imprint replication, high-quality template glue is necessary. Template glue generally refers to a template whose matrix is made of soft materials. Currently, the most commonly used one is soft and transparent polydimethylsiloxane (PDMS) as the molding material to draw micro-nano patterns on the surface; there are also photoresists as prepolymers, using imprint technology to make patterns on its surface, and then through thermal curing or ultraviolet light curing molding, to obtain a polymer soft template for reverse replication of the pattern. Template glue not only has a simple preparation process and greatly saves costs; at the same time, the template glue can compensate for surface morphology differences, thereby greatly improving the quality of imprinting and the area of the imprinted pattern.
[0019] However, the polymer film layer formed after the current nanoimprint template glue is cured has poor mechanical properties and low strength, and cannot adapt to nanoimprinting of multiple angles and different grating structures. In addition, residual glue is prone to breakage during the imprint demolding process, resulting in structural defects, and template glue will remain on the master, increasing the difficulty of cleaning the master. If the master is not thoroughly cleaned to remove the residual template glue, the residual master glue will contaminate the grating structure and even damage the expensive master. In addition, the current template glue produces large deformation after imprinting, which leads to larger differences in optical parameters, thereby affecting optical performance, making it impossible to produce high-precision and high-resolution graphics, and making the uniformity of the prepared products poor.
[0020] To solve the above problems, an embodiment of the present application provides a nanoimprint template glue, which is made of the following raw materials: polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator.
[0021] Among them, the polyurethane modified acrylate resin is a polyurethane modified acrylic resin. Using the polyurethane modified acrylate resin as the main resin can enhance the strength and elasticity of the film layer. The perfluoropolyether acrylate resin is used to provide fluoroether segments for the nanoimprint template glue, which mainly enhances the release and demolding of the film layer, and can also improve the softness of the film layer. The fluorocarbon diluent can be a fluorine-containing diluent, which is not a solvent, and can enhance the release effect of the film layer and improve the viscosity of the system; the multifunctional cross-linking agent mainly plays a role in enhancing the compatibility of the system and the strength of the film layer, and can also reduce the viscosity of the system. The auxiliary agent can be a reactive ultraviolet release auxiliary agent, which is mainly used to improve the release and demolding effect of the film layer; the free radical initiator can include a photoinitiator, which is the core component in the ultraviolet curing system. After being exposed to ultraviolet light, it can initiate the resin or monomer to cure into a film, which can affect the curing rate and degree of curing, thereby directly affecting the various properties of the film layer.
[0022] The embodiment of the present application provides a nanoimprint template glue, which is prepared with polyurethane modified acrylate resin and perfluoropolyether acrylate resin as the main body, and uses polyurethane modified acrylate resin and perfluoropolyether acrylate resin to form a cross-linking monomer, so that the nanoimprint template glue forms a firm three-dimensional cross-linked network after curing, thereby greatly improving the phenomenon of incomplete curing. The introduction of perfluoropolyether acrylate resin can also improve the elasticity and strength of the film layer, and reduce the surface energy of the film layer. After film formation, it can be peeled off as a whole or washed with a solvent, so that the film layer has a good peeling and degumming effect, and can also achieve the removal of residual glue on the master plate, which is conducive to multiple precision imprinting. At the same time, the nanoimprint template glue does not contain conventional solvents, is harmless to the environment and the human body, and the viscosity of the template glue is 50-100mPa.s, has good fluidity, and has a good wetting and leveling effect. After uniform glue, the surface is smooth and flat without foreign matter, has a high transmittance, and is easy to UV cure.
[0023] In some embodiments, by weight percentage, the content of polyurethane modified acrylate resin is 40%-55%, for example: 40%, 45%, 50%, 55%, etc.; the content of perfluoropolyether acrylate resin is 20%-35%, for example: 20%, 25%, 30%, 35%, etc.; the content of fluorocarbon diluent is 15%-25%, for example: 15%, 20%, 22%, 25%, etc.; the content of multifunctional cross-linking agent is 5%-10%, for example: 5%, 7%, 8%, 10%, etc.; the content of auxiliary agent is 1%-3%, for example: 1%, 2%, 3%, etc.; the content of cationic initiator is 1%-5%, for example: 1%, 2%, 5%, etc.; the content of free radical initiator is 1%-2%, for example: 1%, 1.5%, 2%, etc.
[0024] Since the nanoimprint template glue is mainly composed of polyurethane modified acrylate resin and perfluoropolyether acrylate resin, its proportion is relatively high; fluorocarbon diluent is used to enhance the release effect of the film layer and improve the viscosity of the system, so its proportion is generally relatively small compared with polyurethane modified acrylate resin and perfluoropolyether acrylate resin; multi-functional cross-linking agents, additives, cationic initiators and free radical initiators mainly play an auxiliary role, so their proportion is relatively low.
[0025] Exemplarily, the proportion of polyurethane modified acrylate resin in the nanoimprint template glue can be 45%, the proportion of perfluoropolyether acrylate resin in the nanoimprint template glue can be 25%, the proportion of fluorocarbon diluent in the nanoimprint template glue can be 20%, the proportion of multifunctional cross-linking agent in the nanoimprint template glue can be 5%, the proportion of auxiliary agent in the nanoimprint template glue can be 2%, the proportion of cationic initiator in the nanoimprint template glue can be 2%, and the proportion of free radical initiator in the nanoimprint template glue can be 1%.
[0026] In some embodiments, the cured nanoimprint template adhesive comprises a main chain and a plurality of side chains, the main chain comprises a plurality of fluoroether segments and polyurethane segments, and the side chains are fluorine-containing side chains.
[0027] Specifically, the main molecular chain of the cured nanoimprint template glue contains elastic polyurethane segments, which are provided by polyurethane modified acrylate resin, thereby improving the elastic toughness of the cured film layer. The main molecular chain of the cured nanoimprint template glue also contains multiple fluoroether segments, which are provided by perfluoropolyether acrylate resin, thereby enabling the cured film layer to have a lower surface energy, greatly improving the separation and demolding effect of the template glue.
[0028] In some embodiments, the cured nanoimprint template adhesive further contains a plurality of fluorine-containing side chains, and at least two of the fluorine-containing side chains have different lengths.
[0029] Specifically, the cured nanoimprint template glue contains a large number of fluorinated side chains of different lengths, and the fluorinated side chains of different lengths can have different effects on the performance of the nanoimprint template glue. Specifically, the length and content of the fluorinated side chains can be adjusted to achieve precise regulation of the performance of the nanoimprint template glue. For example, in general, the longer the length of the fluorinated side chains, the better the water and oil repellency of the cured nanoimprint template glue. Therefore, the cured nanoimprint template glue contains a large number of fluorinated side chains of different lengths, which can make the nanoimprint template glue have different properties, and at the same time, the cured film layer can have a lower surface energy, which greatly improves the separation and demolding effect of the template glue.
[0030] In some embodiments, the polyurethane modified acrylate resin can be selected from any one or more of the modified difunctional polyurethane acrylate P-2012 of Guangzhou Jingtu Environmental Materials, the modified difunctional polyurethane acrylate P-2018 of Guangzhou Jingtu Environmental Materials, the polyurethane modified acrylate ZHU-1998 of DIC, the polyurethane modified acrylate ZHU-2047 of DIC, and the polyurethane modified acrylate SW201 of Guangzhou Sanwang Chemical.
[0031] Exemplarily, the polyurethane-modified acrylate resins provided above can all be used as the main resin for preparing the nanoimprint template adhesive, and can play a role in enhancing the strength and elasticity of the film layer.
[0032] For example, taking ZHU-1998 as an example, ZHU-1998 can be used for glass substrate processing protection, and has excellent adhesion, scratch resistance, good resistance to cutting fluids, good alkaline film stripping performance, etc. Taking ZHU-2047 as an example, ZHU-2047 can be used for glass and metal protective glue, and has good peeling performance, high paint film strength, good tensile properties, etc. Taking SW201 as an example, SW201 is an organic silicon fluorine modified aliphatic polyurethane acrylate resin, which is a colorless or slightly yellow transparent viscous liquid with a functionality of 6 functional groups and a viscosity of 2200-4500mPa.s. It has good anti-graffiti effect, good compatibility with UV system, high hardness, fast curing speed, and a water drop angle between 108°-110°.
[0033] In some embodiments, the perfluoropolyether acrylate resin can be selected from any one or more of perfluoropolyether methacrylate PFPE-MAA-1000 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-1500 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-2000 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-3000 of Suzhou Cangmu New Materials, Solvay Fluorolink AD1700 and perfluoropolyether methacrylate of Fuzhou Taipuda New Materials.
[0034] The molecular weight of the perfluoropolyether methacrylate of Fuzhou TOPDA New Materials (TOPDA) can be 1000, 2000 or 4000, which is not specifically limited here.
[0035] Exemplarily, the perfluoropolyether acrylate resins provided above can provide fluoroether segments for the nanoimprint template adhesive, and play a role in enhancing the release of the film layer from the mold, and can also improve the softness of the film layer. The perfluoropolyether acrylate resin provided above is a colorless or light yellow transparent liquid, and can be used as a high-performance fluorine-containing polymer monomer that is waterproof and oil-proof.
[0036] In some embodiments, the fluorocarbon diluent can be selected from any one or more of trifluoroethyl acrylate, hexafluorobutyl acrylate, octafluoropentyl acrylate, dodecafluoroheptyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, octafluoropentyl methacrylate, and dodecafluoroheptyl methacrylate.
[0037] Illustratively, the fluorocarbon diluents provided above can enhance the release effect of the film layer and improve the viscosity of the system, so that the film layer has better peeling and degumming effects, and can also remove residual glue from the master plate, which is conducive to multiple precision printing.
[0038] In some embodiments, the multifunctional crosslinking agent can be selected from any one or more of dipropylene glycol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and 1,6-hexanediol diacrylate.
[0039] Illustratively, the multifunctional cross-linking agents provided above can enhance the compatibility and film strength of the system, and can also reduce the viscosity of the system.
[0040] In some embodiments, the auxiliary agent can be any one or more of 2061 of Guangzhou Jingtu Environmental Materials, 2063 of Guangzhou Jingtu Environmental Materials, HY-RC902 of Shanghai Huiyan New Materials, and HY-1203 of Shanghai Huiyan New Materials.
[0041] Exemplarily, the auxiliary agents provided above can improve the release and demolding effect of the film layer, so that the film layer has better peeling and debonding effects, and can also remove residual glue from the master plate, which is conducive to multiple precision printing.
[0042] In some embodiments, the cationic initiator can be any one or more of ANTHRACUREUVS-1331, ANTHRACUREUVS-1101, Easep i 6992, Easep i 1176, and Easep i 250.
[0043] Exemplarily, the cationic initiators provided above are all capable of initiating a cationic polymerization reaction, thereby polymerizing the polyurethane-modified acrylate resin and the perfluoropolyether acrylate resin to generate a nanoimprint template adhesive.
[0044] Exemplarily, ANTHRACUREUVS-1331 is 9,10-dibutoxyanthracene, and its corresponding CAS Registry Number is 76275-14-4. ANTHRACUREUVS-1101 is 9,10-diethoxyanthracene, and its corresponding CAS Registry Number is 68818-86-0. Easep i 6992 is a mixed triarylsulfonium salt, and its corresponding CAS Registry Numbers are 68156-13-8, 74227-35-3 and 108-32-7. Easep i 1176 is a liquid phenyl hexafluoroantimonate sulfonium salt mixed with a monosalt and a disalt, and its corresponding CAS Registry Numbers are 8945-2-37-9 and 71449-78-0.
[0045] In some embodiments, the free radical initiator can be any one or more of 1173, 184, TPO, TPO-L, 127, 369, I TX, BDK, 819, 754, 380, and BMF.
[0046] Exemplarily, the free radical initiators provided above may include photoinitiators, which are the core components in the UV curing system. After being exposed to UV light, they can initiate the resin or monomer to cure into a film, which can affect the curing rate and degree of curing, thereby directly affecting the various properties of the film layer.
[0047] It should be noted that the multiple different types of polyurethane modified acrylate resins, perfluoropolyether acrylate resins, fluorocarbon diluents, multifunctional crosslinking agents, additives and free radical initiators exemplified above generally have different molecular weights, functional groups or hardness, but all belong to the same category of substances.
[0048] See also Figure 1 , Figure 1 1 is a flow chart of an embodiment of a method for preparing a nanoimprint template glue provided in an embodiment of the present application. The preparation method comprises: step S101 and step S102.
[0049] Step S101: providing polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator.
[0050] It should be noted that the specific embodiments of the polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator can refer to the above embodiments and will not be repeated here.
[0051] Step S102: preparing a nanoimprint template adhesive by using polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator.
[0052] The embodiment of the present application provides a method for preparing a nanoimprint template glue, which is prepared with polyurethane modified acrylate resin and perfluoropolyether acrylate resin as the main body, and uses polyurethane modified acrylate resin and perfluoropolyether acrylate resin to form a cross-linking monomer, so that the nanoimprint template glue forms a firm three-dimensional cross-linked network after curing, thereby greatly improving the phenomenon of incomplete curing. The introduction of perfluoropolyether acrylate resin can also improve the elasticity and strength of the film layer, and reduce the surface energy of the film layer. After film formation, it can be peeled off as a whole or washed with a solvent, so that the film layer has a good peeling and degumming effect, and can also achieve the removal of residual glue from the master plate, which is conducive to multiple precision imprinting. At the same time, the nanoimprint template glue does not contain conventional solvents, is harmless to the environment and the human body, and the viscosity of the template glue is 50-100mPa.s, has good fluidity, and has a good wetting and leveling effect. After uniform glue, the surface is smooth and flat without foreign matter, has a high transmittance, and is easy to UV cure.
[0053] In some embodiments, in step S102, a nanoimprint template adhesive is prepared by using polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator, which may include: sub-step S1021 and sub-step S1022, such as Figure 2 shown.
[0054] Sub-step S1021: adding polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional cross-linking agent, and auxiliary agent into a container, and stirring and mixing them uniformly based on a first stirring parameter;
[0055] Sub-step S1022: adding a cationic initiator and a free radical initiator into a container, and stirring and mixing them uniformly based on a second stirring parameter, thereby obtaining a nanoimprint template glue.
[0056] Specifically, polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent and auxiliary agent are added into a container, and stirred and mixed uniformly based on a first stirring parameter, so that the above materials are completely dispersed and dissolved.
[0057] Exemplarily, the first stirring parameter includes a first stirring temperature, a first stirring speed and a first stirring time. The first stirring speed can be 500-1000r / min, the first stirring temperature can be 21°-25°, preferably, the first stirring temperature can be 23°, the first stirring temperature is the liquid temperature in the container during stirring, the first stirring speed is 500r / min and 1000r / min, and the first stirring time is 60 minutes. When stirring and mixing evenly, polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent and auxiliary agent can be added to the container, and slowly stirred at a speed of 500r / min for 30 minutes, and then stirred at a speed of 1000r / min for 30 minutes after the resin is completely dispersed and dissolved, and the liquid temperature in the above-mentioned container is maintained between 21°-25°.
[0058] Specifically, a cationic initiator and a free radical initiator are added into a container, and stirred and mixed evenly based on a second stirring parameter, and then allowed to stand and filtered to obtain a filtered nanoimprint template glue.
[0059] Exemplarily, the second stirring parameter includes a second stirring temperature, a second stirring speed and a second stirring time. The second stirring temperature can be 21°-25°, and the second stirring time can be 30-120 minutes. Preferably, the second stirring temperature can be 23°, the second stirring temperature is the liquid temperature in the container during stirring, the second stirring speed is 1000r / min, and the second stirring time is 120 minutes. When stirring and mixing evenly, the speed can be adjusted to 1000r / min, and then the cationic initiator and the free radical initiator are slowly added, and stirring is continued for 120 minutes, and the liquid temperature in the container is maintained between 21°-25° during the process. After stirring, let it stand for 30 minutes, and then filter under pressure with a 0.22μm organic filter to obtain a colorless or slightly yellow transparent nanoimprint template glue.
[0060] It should be noted that the entire preparation process can be controlled between 21°-25°. If the temperature is too high, such as above 60°C, the stability of some materials such as fluorocarbon diluents will be poor. Filtering after stirring can remove impurities brought by raw materials and glue making equipment. If not filtered, impurities brought by raw materials and glue making equipment may affect the transfer of template glue, affect the imprinting yield, and even damage the expensive imprint master.
[0061] The preparation method and performance of the nanoimprint template glue of the embodiment of the present application are described below through specific examples.
[0062] Embodiment 1:
[0063] (1) Add 25g of P2012, 25g of P-2018, 20g of PFPE-MAA-1000, 8g of hexafluorobutyl methacrylate, 8g of octafluoropentyl methacrylate, 2g of dipropylene glycol diacrylate, 4g of trimethylolpropane triacrylate, and 2g of 2061 into a 150mL container and stir slowly at a speed of 500r / min for 30 minutes. After the resin is completely dispersed and dissolved, stir at a speed of 1000r / min for 30 minutes. Maintain the liquid temperature in the container between 21° and 25°.
[0064] (2) Add 1 g of 184 and 5 g of ANTHRACURE UVS-1331 into the above container and continue stirring at a speed of 1000 r / min for 2 hours. During the process, maintain the liquid temperature in the container at 23°C.
[0065] (3) After stirring, filter under pressure using a 0.22 μm organic filter to obtain a colorless or slightly yellow transparent nanoimprint template glue.
[0066] Therefore, in Example 1, the amount of polyurethane modified acrylate resin accounts for 50%, the amount of perfluoropolyether acrylate resin accounts for 20%, the amount of fluorocarbon diluent accounts for 16%, the amount of multifunctional cross-linking agent accounts for 6%, the amount of auxiliary agent accounts for 2%, the amount of cationic initiator accounts for 5%, and the amount of free radical initiator accounts for 1%.
[0067] Embodiment 2:
[0068] (1) Add 40g of SW210, 15g of PFPE-MAA-1000, 20g of PFPE-MAA-2000, 8g of trifluoroethyl acrylate, 7g of hexafluorobutyl acrylate, 2g of propoxylated glycerol triacrylate, 3g of 1,6-hexanediol diacrylate, and 1g of 2063 into a 150mL container and stir slowly at a speed of 500r / min for 30 minutes. After the resin is completely dispersed and dissolved, stir at a speed of 1000r / min for 30 minutes. Maintain the liquid temperature in the container between 21° and 25°.
[0069] (2) Add 2 g of TPO and 2 g of ANTHRACURE UVS-1101 into the above container and continue stirring at a speed of 1000 r / min for 0.5 hours. During the process, maintain the liquid temperature in the container at 23°C.
[0070] (3) After stirring, filter under pressure using a 0.22 μm organic filter to obtain a colorless or slightly yellow transparent nanoimprint template glue.
[0071] Therefore, in Example 2, the amount of polyurethane modified acrylate resin accounts for 40%, the amount of perfluoropolyether acrylate resin accounts for 35%, the amount of fluorocarbon diluent accounts for 15%, the amount of multifunctional cross-linking agent accounts for 5%, the amount of auxiliary agent accounts for 1%, the amount of cationic initiator accounts for 2%, and the amount of free radical initiator accounts for 2%.
[0072] Embodiment 3:
[0073] (1) Add 55g of ZHU-1998, 20g of PFPE-MAA-1500, 15g of dodecafluoroheptyl acrylate, 5g of neopentyl glycol diacrylate, and 3g of HY-RC902 into a 150mL container and stir slowly at 500r / min for 30 minutes. After the resin is completely dispersed and dissolved, stir at 1000r / min for 30 minutes. Maintain the liquid temperature in the container between 21° and 25°.
[0074] (2) Add 1 g of 127 and 1 g of Easepi 6992 into the above container and continue stirring at a speed of 1000 r / min for 1 hour. During the process, maintain the liquid temperature in the container at 23°C.
[0075] (3) After stirring, filter under pressure using a 0.22 μm organic filter to obtain a colorless or slightly yellow transparent nanoimprint template glue.
[0076] Therefore, in Example 3, the amount of polyurethane modified acrylate resin accounts for 55%, the amount of perfluoropolyether acrylate resin accounts for 20%, the amount of fluorocarbon diluent accounts for 15%, the amount of multifunctional cross-linking agent accounts for 5%, the amount of auxiliary agent accounts for 3%, the amount of cationic initiator accounts for 1%, and the amount of free radical initiator accounts for 1%.
[0077] Embodiment 4:
[0078] (1) Add 40g of ZHU-2047, 20g of PFPE-MAA-3000, 25g of dodecafluoroheptyl acrylate, 10g of tripropylene glycol diacrylate, and 2g of HY-1203 into a 150mL container and stir slowly at 500r / min for 30 minutes. After the resin is completely dispersed and dissolved, stir at 1000r / min for 30 minutes. Maintain the liquid temperature in the container between 21° and 25°.
[0079] (2) Add 1 g of 369 and 2 g of Easepi 1176 into the above container and continue stirring at a speed of 1000 r / min for 1 hour. During the process, maintain the liquid temperature in the container at 23°C.
[0080] (3) After stirring, filter under pressure using a 0.22 μm organic filter to obtain a colorless or slightly yellow transparent nanoimprint template glue.
[0081] Therefore, in Example 4, the amount of polyurethane modified acrylate resin accounts for 40%, the amount of perfluoropolyether acrylate resin accounts for 20%, the amount of fluorocarbon diluent accounts for 25%, the amount of multifunctional cross-linking agent accounts for 10%, the amount of auxiliary agent accounts for 2%, the amount of cationic initiator accounts for 2%, and the amount of free radical initiator accounts for 1%.
[0082] The nanoimprint template glue provided in the above embodiment was used for performance testing, and the performance test experimental data are shown in Table 1. The specification values in Table 1 are the specification values of the nanoimprint template glue in the related art, and the specification values are used to compare with the nanoimprint template glue provided in the above embodiment to confirm whether the nanoimprint template glue provided in the above embodiment meets the specification values.
[0083] Table 1
[0084]
[0085]
[0086] Since the nanoimprint template glue provided by the present application can form a strong three-dimensional cross-linked network after curing, it can greatly improve the phenomenon of incomplete curing, and can also improve the elasticity and strength of the film layer, and reduce the surface energy of the film layer. After film formation, it can be peeled off as a whole or washed with a solvent, so that the film layer has a good peeling and degumming effect, and can also remove the residual glue of the master plate, which is conducive to multiple precision imprinting. Therefore, the template glue requires a larger surface water drop angle, better demoulding structure integrity and cleaning effect.
[0087] As can be seen from Table 1, the appearance of the nanoimprint template glue provided in the embodiment of the present application meets the standard value of a transparent or slightly turbid liquid; the viscosity meets the standard value of 50-100mPa.s; the hardness after curing meets the standard value of 50-65D; the surface water drop angle meets the standard value greater than or equal to 105°; the tensile strength meets the standard value greater than or equal to 3MPa; the elongation at break meets the standard value greater than or equal to 25%; the Young's modulus meets the standard value greater than or equal to 15MPa; the integrity of the demolding structure meets the standard value greater than or equal to 10 times of transfer; the conformal performance meets the standard value less than or equal to ±5%; the film layer can be completely demolded when the thickness is 30μm, and the film layer can be completely debonded by immersion in a solvent when the thickness is 2μm. It can be seen that the nanoimprint template glue provided in the embodiment of the present application can achieve a better cleaning effect, can be peeled off as a whole or cleaned with a solvent, so that the film layer has a better peeling and debonding effect, and can also remove the residual glue of the master plate, which is conducive to multiple precision imprinting.
[0088] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A nanoimprint template glue, characterized in that: The nano-imprint template glue is prepared from the following raw materials: polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional cross-linking agent, auxiliary agent, cationic initiator and free radical initiator.
2. The nanoimprint template glue according to claim 1, characterized in that: In weight percentage, the content of the polyurethane modified acrylate resin is 40%-55%, the content of the perfluoropolyether acrylate resin is 20%-35%, the content of the fluorocarbon diluent is 15%-25%, the content of the multifunctional cross-linking agent is 5%-10%, the content of the auxiliary agent is 1%-3%, the content of the cationic initiator is 1%-5%, and the content of the free radical initiator is 1%-2%.
3. The nanoimprint template glue according to claim 1, characterized in that: The cured nanoimprint template glue comprises a main chain and a plurality of side chains, wherein the main chain comprises a plurality of fluoroether segments and polyurethane segments, and the side chains are fluorine-containing side chains.
4. The nanoimprint template glue according to claim 3, characterized in that: At least two of the fluorine-containing side chains have different lengths.
5. The nanoimprint template glue according to claim 1, characterized in that: The polyurethane modified acrylate resin is at least one of the modified difunctional polyurethane acrylate P-2012 of Guangzhou Jingtu Environmental Materials, the modified difunctional polyurethane acrylate P-2018 of Guangzhou Jingtu Environmental Materials, the polyurethane modified acrylate ZHU-1998 of DIC, the polyurethane modified acrylate ZHU-2047 of DIC, and the polyurethane modified acrylate SW201 of Guangzhou Sanwang Chemical.
6. The nanoimprint template glue according to claim 1, characterized in that: The perfluoropolyether acrylate resin is at least one of perfluoropolyether methacrylate PFPE-MAA-1000 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-1500 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-2000 of Suzhou Cangmu New Materials, perfluoropolyether methacrylate PFPE-MAA-3000 of Suzhou Cangmu New Materials, Solvay Fluorolink AD1700 and perfluoropolyether methacrylate of Fuzhou Taipuda New Materials.
7. The nanoimprint template glue according to claim 1, characterized in that: The fluorocarbon diluent is at least one of trifluoroethyl acrylate, hexafluorobutyl acrylate, octafluoropentyl acrylate, dodecafluoroheptyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, octafluoropentyl methacrylate, and dodecafluoroheptyl methacrylate.
8. The nanoimprint template glue according to claim 1, characterized in that: The multifunctional crosslinking agent is at least one of dipropylene glycol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and 1,6-hexanediol diacrylate.
9. The nanoimprint template glue according to claim 1, characterized in that: The auxiliary agent is at least one of 2061 of Guangzhou Jingtu Environmental Materials, 2063 of Guangzhou Jingtu Environmental Materials, HY-RC902 of Shanghai Huiyan New Materials, and HY-1203 of Shanghai Huiyan New Materials.
10. The nanoimprint template glue according to claim 1, characterized in that: The cationic initiator is at least one of ANTHRACUREUVS-1331, ANTHRACUREUVS-1101, Easepi 6992, Easepi 1176, and Easepi 250.
11. The nanoimprint template glue according to claim 1, characterized in that: The free radical initiator is at least one of 1173, 184, TPO, TPO-L, 127, 369, ITX, BDK, 819, 754, 380, and BMF.
12. A method for preparing a nanoimprint template glue, characterized in that: The preparation method comprises: Provide polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator; The nanoimprint template adhesive is prepared by using the polyurethane modified acrylate resin, perfluoropolyether acrylate resin, fluorocarbon diluent, multifunctional crosslinking agent, auxiliary agent, cationic initiator and free radical initiator.
13. The preparation method according to claim 12, characterized in that: The method of preparing the nanoimprint template adhesive by using the polyurethane modified acrylate resin, the perfluoropolyether acrylate resin, the fluorocarbon diluent, the multifunctional crosslinking agent, the auxiliary agent, the cationic initiator and the free radical initiator comprises: Adding the polyurethane modified acrylate resin, the perfluoropolyether acrylate resin, the fluorocarbon diluent, the multifunctional crosslinking agent and the auxiliary agent into a container, and stirring and mixing them uniformly based on a first stirring parameter; The cationic initiator and the free radical initiator are added into the container, and stirred and mixed evenly based on a second stirring parameter to obtain the nanoimprint template glue.
14. The preparation method according to claim 13, characterized in that: The first stirring parameters include a first stirring temperature, a first stirring speed and a first stirring time, the first stirring temperature is 21°-25°, the first stirring speed is 500-1000r / min, and the first stirring time is 60 minutes; the second stirring parameters include a second stirring temperature, a second stirring speed and a second stirring time, the second stirring temperature is 21°-25°, the second stirring speed is 1000r / min, and the second stirring time is 30-120 minutes.
